Defining Recovery in Chronic Whiplash: A Qualitative Study. Issue 7 (July 2020) - Griffin, Alexandra R.; Moloney, Niamh; Leaver, Andrew; Jagnoor, Jagnoor; Michaleff, Zoe A.; Lin, Chung-Wei Christine; Trudy, Rebbeck
Abstract : Objective: The meaning of recovery from musculoskeletal injury is complex, and understanding recovery from whiplash may be particularly important, given the chronic, often recalcitrant nature of the condition. Gaining a better understanding of recovery may also aid in the development and interpretation of future clinical trials. The aim of this study was to define the meaning of recovery from whiplash, and the factors influencing recovery, by exploring the perceptions of people with chronic whiplash, and their treating physiotherapists. Materials and Methods: This qualitative study was embedded within a larger randomized-controlled trial, and consisted of semistructured interviews. Interviews were conducted with 13 patient participants with chronic whiplash and 7 physiotherapists. Patient participants were asked what recovery meant to them, and perceptions around barriers and facilitators to recovery were explored. Physiotherapists were also asked to share their beliefs on the meaning of recovery, and what they believe recovery means to their patients. Results: Both patient participants and physiotherapists perceived recovery to be defined within the themes of pain, function, and emotional well-being. Patient participants also identified self-perception as important, whereas physiotherapists identified ownership on the part of the patient, and the multidimensional nature of recovery, including cultural values and beliefs, as important. Several themes relating to barriers and facilitators to recovery were also identified, and included personal and social characteristics and aspects of the therapeutic relationship. Discussion: Recovery is a multidimensional and complex construct. In addition to pain intensity and disability, measurement and conceptualization of recovery should focus on emotional well-being, self-perception, and the cultural values and beliefs of the individual. A positive therapeutic relationship, with attention to psychological and social influences, appears to be important in facilitating recovery and well-being. Abstract : Supplemental Digital Content is available in the text.